Computerized dynamic testing of children's potential for reasoning by analogy: The role of executive functioning. - Vogelaar, Bart; Veerbeek, Jochanan; Splinter, Suzanne E.; Resing, Wilma C. M. (Journal of Computer Assisted Learning, 2021)
This study aimed to investigate children's potential for reasoning by analogy utilizing a newly‐developed computerized dynamic test, and the potential differential influence of executive functions (cognitive flexibility, attention, and planning) on static and dynamic measures of analogical reasoning. Participants included 64 children (mean age = 7.55). The study employed a two‐session experimental test‐training‐test design. Based on randomized blocking, half of the children received a graduated prompts training between pre‐test and post‐test, and the other half did not. Trained children improved more than control children in both their accuracy scores and number of accurately applied transformations from pre‐test to post‐test. It was further found that cognitive flexibility, attention and planning, is associated with successful solving of analogies. Training children in analogical reasoning seemed to reduce the effect of executive functions. It was also found that that children who were more cognitively flexible needed more prompts during the training. Lay Description: What is already known about this topic: Analogical reasoning is of great importance to scholastic performance and everyday learning.Computerized dynamic tests are promising for measuring children's potential for analogical reasoning.Executive functions have been found to influence analogical reasoning performance.Dynamic testing compensates for the influence of executive functions What this paper adds: A newly developed computerized dynamic test of analogical reasoning can detect individualized learning paths and instructional needs of children of various ability levels.Training children in analogical reasoning as part of a computerized dynamic test seems to reduce the effect of executive functioning.Children's instructional needs are related to cognitive flexibility. Implications for practice and/or policy: Computerized dynamic testing of analogical reasoning is a useful instrument for identification purposes.These tests provide information about children's problem‐solving behaviour, and the type and number of instructions they need when solving new tasks, offering insights relevant for individualized education plans.Individual differences in children's (improvements in) analogical reasoning seem to be related to their executive functioning.